2022
DOI: 10.3390/su14148617
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive Study Behaviors Are Associated with Eating Disorders and Have Independent Negative Effects on Well-Being: A Structural Equation Model Study among Young Musicians

Abstract: Compulsive overworking and eating disorders (EDs) show considerable similarities in terms of risk factors (e.g., rigid perfectionism), clinical manifestation (e.g., excessive controlling behaviors), and consequences (e.g., physical exhaustion and depression). This study aimed to examine the hypotheses that compulsive study behaviors (conceptualized as study addiction) are related to EDs and that they have independent negative effects on well-being among young musicians, who constitute a highly vulnerable popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…It is particularly evident in relation to OCPD, in which case it was substantially more strongly associated with well-being and loneliness than a personality disorder. Similar, the independent effects of study addiction on well-being were found in a study of its associations with eating disorders (Woropay-Hordziejewicz et al, 2022).…”
Section: Implications Of Compulsive Study Behaviors Unrelated To Ocpdsupporting
confidence: 73%
See 3 more Smart Citations
“…It is particularly evident in relation to OCPD, in which case it was substantially more strongly associated with well-being and loneliness than a personality disorder. Similar, the independent effects of study addiction on well-being were found in a study of its associations with eating disorders (Woropay-Hordziejewicz et al, 2022).…”
Section: Implications Of Compulsive Study Behaviors Unrelated To Ocpdsupporting
confidence: 73%
“…These results are congruent with (1) the theoretical framework conceptualizing study addiction as a construct separate from OCPD (P. A. Atroszko, 2022b); (2) previous studies showing its considerable negative association with well-being among music academy students (Czerwiński et al, 2022;Lawendowski et al, 2020), as well as high-school and general undergraduate student samples (P. A. Atroszko, 2022aAtroszko, , 2022bWróbel, 2020); and (3) results showing the negative effects of study addiction on wellbeing independently of other mental health problems such as eating disorders (Woropay-Hordziejewicz et al, 2022). The current results also strongly support the previously emphasized need to control for learning engagement whenever study addiction is investigated and vice versa (P. A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Problematic overstudying has been conceptualized as an early form of work addiction which has a relatively long-standing history of research (Atroszko, 2015(Atroszko, , 2022a. Problematic overstudying has also been called "study addiction" (Atroszko et al, 2015) or "compulsive study behaviour" (Woropay- Hordziejewicz et al, 2022). So far, systematic studies, including cross-cultural longitudinal surveys, substantiate that study addiction is an early form of work addiction (Atroszko et al, 2016a; see Atroszko, 2022a).…”
Section: Introductionmentioning
confidence: 99%